Case Report: Afatinib Sensitivity in Rare EGFR E746_L747delinsIP Mutated LUAD With Peritoneal Metastases - Zhang, Lili; Yang, Lu; Sun, Binxu; Deng, Yixiao; Yang, Jie; Wu, Dongfang; Kong, Fanming (Frontiers in Oncology, 2022)
Non-small cell lung cancer (NSCLC) patients harboring the epidermal growth factor receptor (EGFR) sensitive mutations are known to benefit significantly from EGFR tyrosine kinase inhibitors (TKIs), such as erlotinib, gefitinib, icotinib, or afatinib. Still, the efficacy of EGFR-TKI against rare mutations has been less well investigated. Here, we report a female patient with advanced lung adenocarcinoma (LUAD), carrying a rare mutation of EGFR Exon19 E746_L747delinsIP, administrated with the first-generation EGFR-TKIs at the first line, and the patient continued to progress slowly until peritoneal metastases. Subsequently, the patient was treated with anlotinib for five months until disease progression. Given the finding of the same EGFR rare mutation in peritoneal effusion without other EGFR-TKIs resistance mutations, the patient received afatinib with a tremendous response. Our results may be of clinical relevance for those LUAD patients carrying this rare mutation, and these findings warrant further investigation.